A Novel Program to Improve Cognitive Function in Individuals With Dementia Using Transcranial Alternating Current Stimulation (tACS) and Tutored Cognitive Exercises - Moussavi, Zahra; Kimura, Kazushige; Kehler, Lonnie; de Oliveira Francisco, Cristina; Lithgow, Brian (Frontiers in Aging, 2021)
The effects of cognitive exercises on healthy and aging population has been of great interest and controversy. On the other hand, while transcranial alternating current stimulation (tACS) is considered a promising tool for modulating brain oscillation, research lacks on its long-lasting therapeutic effect. In this pilot study, for the first time, we explore the effect of a regimen of cognitive exercises using the MindTriggers app with and without tACS on older adults with dementia. The study groups were 28 individuals (age 56 to 83 years) enrolled into two groups: Exr Group, who received cognitive exercises only and Exr+tACS Group who received tACS at 40 Hz simultaneously with cognitive exercises for a period of 4 consecutive weeks, 5days/week, two 30min-sessions/day; all the training sessions were tutored. They were assessed at pre and post intervention and also one month after the end of trial (follow-up) with an independent assessment (WMS-IV) as the primary outcome measure. The results show significant improvement at post-intervention in both groups, while the Exr+tACS protocol lead to superior improvement at follow-up session. The most important outcomes of this study are twofold: 1) The tutored repeated practice of the MindTriggers app exercises does significantly improve the cognitive functions of older adults with dementia and that improvement lasts for at least one month after the end of the intervention, and 2) The application of tACS improves the positive effects of cognitive exercises with the positive effect lasting a longer period of time; in other wordswe speculate that it may lead to long-term potentiation.